2022
DOI: 10.1111/josi.12572
|View full text |Cite
|
Sign up to set email alerts
|

Social relationships, stigma, and wellbeing through experiences of homelessness in the United Kingdom

Abstract: People occupying stigmatized social positions often withdraw from sources of social support, becoming stressed, depressed, and isolated. Homelessness is globally prevalent and stigmatized. Despite the overwhelming evidence that homelessness is associated with experiences of isolation and poor mental health, there is a sparse understanding of how stigma and social relationships interact with mental health in this context. This mixed-method study presents evidence that relationship breakdown is a common preceden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 77 publications
1
15
0
1
Order By: Relevance
“…Also, Supplementary Analysis 3 in Data S1 showed that the identity ties did not moderate the negative effect of social exclusion on resignation, confirming that the identity bonds with other homeless were not an effective source of protection against social threats. The results align with the research from Rea (2022), showing that social support from homeless friends was not associated with better mental health. These latter findings align with the literature confronting the rejection‐identification model in low‐status marginalized groups (e.g., Bilewicz et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Also, Supplementary Analysis 3 in Data S1 showed that the identity ties did not moderate the negative effect of social exclusion on resignation, confirming that the identity bonds with other homeless were not an effective source of protection against social threats. The results align with the research from Rea (2022), showing that social support from homeless friends was not associated with better mental health. These latter findings align with the literature confronting the rejection‐identification model in low‐status marginalized groups (e.g., Bilewicz et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, results confirmed that the centrality of the identification with one's low-status group could make experiences of discrimination and social exclusion more salient (e.g., Begeny & Huo, 2017;Bilewicz et al, 2021;Rea, 2022;Rubin & Stuart, 2018). Indeed, scholars argued that, when highly central and relevant to the self, the marginalized identity can promptly become the cognitive schema through which individuals interpret their social experiences.…”
Section: Gen Er a L Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The data were obtained as part of a larger dataset which examined differences in values, self-mastery, social support, interpersonal trust and well-being between people experiencing homelessness and other groups within the United Kingdom (Rea, 2019). The recruitment procedure, details of participant recruitment numbers by centre, respective participant payments and data-cleansing procedure are fully reported and can be reviewed in Rea (2023).…”
Section: Methodsmentioning
confidence: 99%